Functional elements of the cis-regulatory lincRNA-p21 - Winkler, Lauren; Jimenez, Maria; Zimmer, Joshua T.; Williams, Adam; Simon, Matthew D.; Dimitrova, Nadya (Cell reports (Cambridge), 2022)
The p53-induced long noncoding RNA (lncRNA) lincRNA-p21 is proposed to act in cis to promote p53-dependent expression of the neighboring cell cycle gene, Cdkn1a/p21. The molecular mechanism through which the transcribed lincRNA-p21 regulatory locus activates p21 expression remains poorly understood. To elucidate the functional elements of cis-regulation, we generate a series of genetic models that disrupt DNA regulatory elements, the transcription of lincRNA-p21, or the accumulation of mature lincRNA-p21. Unexpectedly, we determine that full-length transcription, splicing, and accumulation of lincRNA-p21 are dispensable for the chromatin organization of the locus and for cis-regulation. Instead, we find that production of lincRNA-p21 through conserved regions in exon 1 of lincRNA-p21 promotes cis-activation. These findings demonstrate that the activation of nascent transcription from this lncRNA locus, but not the generation or accumulation of a mature lncRNA transcript, is necessary to enact local gene expression control. [Display omitted] •p53 regulates the neighboring p21 and lincRNA-p21 cooperatively•Production of nascent lincRNA-p21 promotes p21 expression in cis•Conserved elements in nascent lincRNA-p21 contribute to cis-activation•Transcription, processing, and accumulation of full-length lincRNA-p21 are dispensable Winkler et al. analyze a series of genetic models to show that full-length production, splicing, and transcript accumulation of the long noncoding RNA lincRNA-p21 are dispensable for its role as a transcriptional activator of the neighboring gene p21. Instead, nascent transcription through conserved regions of lincRNA-p21 is sufficient for cis-activation.